2012
DOI: 10.1159/000339341
|View full text |Cite
|
Sign up to set email alerts
|

Interest of High-Dose Pulse Corticosteroid Therapy Combined with Methotrexate for Severe Alopecia Areata: A Retrospective Case Series

Abstract: Background: The combination of systemic pulse corticosteroids and methotrexate in the treatment of severe alopecia areata has never been reported. Objective: The objective of this work was to give arguments for the efficacy and safety of this combined treatment. Methods: This was a retrospective case series of patients treated with intravenous 500 mg methylprednisolone per day for 3 consecutive days monthly during 3 months plus methotrexate initiated at the end of the second pulse regimen. We reviewed all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 28 publications
2
46
1
1
Order By: Relevance
“…Indeed, in our cohort, 4/6 patients benefited from a second course. Combining pulse therapy with low-dose oral cyclosporine [32] or methotrexate [33,34] may also increase probability of long-term remission. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our cohort, 4/6 patients benefited from a second course. Combining pulse therapy with low-dose oral cyclosporine [32] or methotrexate [33,34] may also increase probability of long-term remission. …”
Section: Discussionmentioning
confidence: 99%
“…Although no randomized controlled study has been found, MTX and low doses of oral corticosteroids might be an effective treatment for resistant AA, which should be evaluated in larger series [28,47,48].…”
Section: Methotrexatementioning
confidence: 99%
“…In combination with steroids, the different schemes that have been used are: 1) 500 mg i.v. methylprednisolone per day for 3 consecutive days, monthly, during 3 months plus MTX initiated at a dose of 12.5 mg/week and increased up to 25 mg/week [78]. 2) Prednisone at 10 or 20 mg/day and MTX at 15 mg weekly [79].…”
Section: Methotrexatementioning
confidence: 99%